Quantification of medicinally valuable weeds in oil palm plantations of Kerala - Sarada, S.; Sreekandan Nair, G.; Reghunath, B.R. (Journal of Tropical Agriculture, 2006)
The medicinally valuable weeds naturally growing in young, medium and mature plantations of oil palm were identified and quantified by stratified random sampling technique. Quantification of plants was done in comparison with that in the open condition. Chrysopogon aciculatus Trin. dominates in all the four strata. Naregamia alata Wight & Arn. is another dominant species in mature plantation. Hemidesmus indicus R. Br. occurs frequently in all the four strata. Another frequently occurring species in young oil palm plantation is Elephantopus scaber Linn, and in medium plantations is Chromolaena odorata King & Robinson. Phyllanthus amarus Schum.& Thonn. is very frequent in medium plantation and open condition. Holostemma adakodien Schult occurs frequently in mature plantation. Young oil palm plantation and open condition were found to be the most similar strata whereas mature plantation and open condition were the most dissimilar strata in vegetation pair-wise analysis. Medium oil palm plantation was found to have high concentration of dominance. Species diversity was the highest in mature oil palm plantation. Species evenness was maximum in open condition.